When function meets emotion, change can happen: Societal value propositions and disruptive potential in fintechs. (November 2019) - Lehner, Othmar M; Simlinger, Romina
Fintechs, as providers of digital service innovations and as highly relevant and novel channels through which to deliver entrepreneurial finance based on the creative use of state-of-the-art technology in the financial domain, have thus far mainly been addressed in research by examining the functional aspects of their value propositions (VPs). This article thus sets out to gain insights into the interplay and overall role of societal VPs as potential antecedents and change catalysts in the formation of the often promised disruptive potential of fintechs for the financial sector. In an inductive, theory-building approach, the authors first examine how societal VPs transcend individual functional and emotional ones for entrepreneurs, and conclude with a conceptual model of how the former can build up the disruptive potential of fintechs and deliver apt solutions for entrepreneurs seeking finance.